Can pro-growth policies lift all boats? An analysis based on household disposable income - Causa, Orsetta (OECD Publishing, 2015)
In a majority of OECD countries, GDP growth over the past three decades has been associated with growing income disparities. To shed some lights on the potential sources of trade-offs between growth and equity, this paper investigates the long-run impact of structural reforms on GDP per capita and household income distribution. Pro-growth reforms can be distinguished according to whether they are found to generate an increase or a reduction in household disposable income inequality. Those that contribute to reduce inequality include the reduction in regulatory barriers to competition, trade and FDI, as well as the stepping-up in job search assistance and training programmes. Conversely, a tightening of unemployment benefits for the long-term unemployed is found to lift mean household income but to lower income among poorer households, thus raising inequality. Several other reforms have no significant impact on income distribution. JEL Classification: 047, D37, E61 Keywords: Growth, inequality, pro-growth policies